2022
DOI: 10.1161/jaha.121.024229
|View full text |Cite
|
Sign up to set email alerts
|

Need for Better and Broader Training in Cardio‐Obstetrics: A National Survey of Cardiologists, Cardiovascular Team Members, and Cardiology Fellows in Training

Abstract: Background Team‐based models of cardio‐obstetrics care have been developed to address the increasing rate of maternal mortality from cardiovascular diseases. Cardiovascular clinician and trainee knowledge and comfort with this topic, and the extent of implementation of an interdisciplinary approach to cardio‐obstetrics, are unknown. Methods and Results We aimed to assess the current state of cardio‐obstetrics knowledge, practices, and services provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 24 publications
2
20
0
1
Order By: Relevance
“…A recent survey of US cardiologists, CV team members, and trainees showed that although CVD is the number‐one cause of pregnancy‐related deaths in the United States, there are significant gaps in knowledge and confidence among providers pertaining to care of pregnant and postpartum women with CVD. This finding supports the need for developing new standards for training and educating members of the cardiology and obstetrics workforce to optimize the care provided to young mothers, and to facilitate the expansion of dedicated cardio‐obstetrics centers 20 . These efforts will improve the care we provide to women at risk for CVD who are planning or experiencing pregnancy and may help reverse the alarming increase in rates of maternal morbidity and mortality experienced in the United States.…”
Section: Cardiovascular Risk Factors In Womenmentioning
confidence: 55%
See 1 more Smart Citation
“…A recent survey of US cardiologists, CV team members, and trainees showed that although CVD is the number‐one cause of pregnancy‐related deaths in the United States, there are significant gaps in knowledge and confidence among providers pertaining to care of pregnant and postpartum women with CVD. This finding supports the need for developing new standards for training and educating members of the cardiology and obstetrics workforce to optimize the care provided to young mothers, and to facilitate the expansion of dedicated cardio‐obstetrics centers 20 . These efforts will improve the care we provide to women at risk for CVD who are planning or experiencing pregnancy and may help reverse the alarming increase in rates of maternal morbidity and mortality experienced in the United States.…”
Section: Cardiovascular Risk Factors In Womenmentioning
confidence: 55%
“…This finding supports the need for developing new standards for training and educating members of the cardiology and obstetrics workforce to optimize the care provided to young mothers, and to facilitate the expansion of dedicated cardio‐obstetrics centers. 20 These efforts will improve the care we provide to women at risk for CVD who are planning or experiencing pregnancy and may help reverse the alarming increase in rates of maternal morbidity and mortality experienced in the United States.…”
Section: Cardiovascular Risk Factors In Womenmentioning
confidence: 99%
“…8 A recent national survey of cardiologists, cardiovascular team members and cardiology fellows in training, identified that over 75% of respondents lacked access to a dedicated cardio-obstetrics team, and only 29% of cardiologists received didactics on cardio-obstetrics during training, suggesting that augmentation of cardioobstetrics education is needed to reduce the large knowledge gaps that exist among clinicians. 18 These data also identify a need for more education, both for physicians and for patients, on recognizing the association between APOs and long-term CVD risk in mothers. 6 When analyzing data from a multiracial cohort of postpartum individuals, the prevalence of self-reported screening and diagnosis of PPD was 82% and 13%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…10 Subspecialists across the internal medicine disciplines of rheumatology, pulmonary and critical care medicine, gastroenterology/transplant hepatology, cardiology, nephrology, endocrinology, infectious disease, and hematology-oncology, indicate that they do not have the basic knowledge, skills, or resources to manage disease-related aspects of sexual and reproductive health (SRH). [13][14][15][16][17][18][19][20][21][22] Our collective of multidisciplinary subspecialty clinicians and health services researchers has described some of the common challenges that subspecialists feel undermine their provision of SRH…”
mentioning
confidence: 99%
“…across the internal medicine disciplines of rheumatology, pulmonary and critical care medicine, gastroenterology/transplant hepatology, cardiology, nephrology, endocrinology, infectious disease, and hematology-oncology, indicate that they do not have the basic knowledge, skills, or resources to manage disease-related aspects of sexual and reproductive health (SRH). [13][14][15][16][17][18][19][20][21][22] Our collective of multidisciplinary subspecialty clinicians and health services researchers has described some of the common challenges that subspecialists feel undermine their provision of SRH care. 4,14,23,24 Our qualitative research also indicates that many patients with chronic diseases feel that their SRH needs are not met in the current subspecialty care model [25][26][27][28] ; they overwhelmingly desire for their subspecialists to address their SRH as it relates to their diseases, but with a holistic approach that accounts for the greater context of their values, preferences, and life circumstances.…”
mentioning
confidence: 99%